Retinoblastoma intravitreal chemotherapy (five-year experience) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Local intravitreal chemotherapy (IVC) is one of the new retinoblastoma (RB) salvage eye methods. However, IVC indications, doses and algorithm of cytostatic application are still not developed, complications and efficacy of this method are not enough studied.Purpose. To study the short-term and long-term results of IVC in RB complex salvage eye treatment.Material and methods. IVC was Melphalan was given to 67 children aged 2 -14 y/o (average 19.2±16.5 mo) inn 91 eyes with RB T1 — T3b stages. 2 groups were selected depending on a dose and IVC method: the 1st group (16 eyes) — the dose was 0.015mg of Melphalan in 1 injection secondary in pretreated RB cases, the 2nd group (75 eyes) — the dose was 0.01 mg of Melphalan in 1 injection as primary therapy in combination with systemic chemoreduction [3]. Follow up from 2 to 5 years (average 20.3±9.1 mo) was in 32 patients (42 eyes).Results. In the 1st group the amount of complications and enucleations was evidence of insufficient efficacy of the second IVC. In this connection the method of combined RB polychemotherapy (PCT) — primary IVC with Melphalan in the dose O.01 mg with simultaneous chemoreduction of CEV-protocol (Patent of Ukraine A61f 9/007 of 27.12.2010) and algorithm of its administration every 3 weeks with additional focal tumor destruction if necessary was developed. Complications were practically not observed except local retinal degeneration in the injection areas (15 eyes). 78.6 % of the eyes were preserved: in the T1-T2 stages — 100 %, T3 (including T3a-T3b) — 65.4 %.Conclusion. Due to our five-year’s experience the developed method of primary IVC in combination with systemic Carboplatin PCT gives the greatest chance for eye and sight preservation with minimal amount of complications and cytostatic drug local and general toxic influence.
Keywords: retinoblastoma; intravitreal chemotherapy; combined polychemotherapy